The Effect of Digitalization on the Sustainability of Accounting Practices in the Financial Industry - Napisah, Lilis Saidah; Taufikurochman, Cecep; Harto, Budi (Yayasan Gema Bina Nusantara, 2024)
This research aims to examine the effect of digitalization on the sustainability of accounting practices in the financial industry. Using a qualitative approach, this research conducted case studies on several leading companies in the financial sector. We collected data on the implementation of digital technologies in accounting practices through in-depth interviews, participatory observation, and document analysis. The research findings show that digitalization brings significant changes in accounting practices, especially with regard to improving efficiency, transparency, and data accuracy. Research has proven that the integration of technologies like cloud-based accounting information systems, big data, and artificial intelligence enhances the quality of financial decision-making. In addition, digitalization also has a positive impact on environmental sustainability through reduced paper usage and energy efficiency. However, the research also reveals challenges, such as the need to upskill accountants, data security issues, and adapt to regulatory changes. The findings provide important insights for practitioners and policymakers in responding to the dynamics brought about by digitalization in accounting. This research contributes to the literature relating to the interaction between technology and accounting practices by providing an in-depth understanding of how financial firms adapt and utilize technological innovations for their business sustainability. The practical implications of this research include recommendations for the development of policies that support the integration of technology in accounting as well as the development of appropriate human resources.